2019
DOI: 10.1002/dmrr.3244
|View full text |Cite
|
Sign up to set email alerts
|

Microangiopathy: Is it relevant to wound healing in diabetic foot disease?

Abstract: Chronic diabetic complications – both microvascular and macrovascular – have become serious health issues with their increasing prevalence paralleling the dramatic rise of the diabetic population worldwide. Of these complications, foot disease is a major cause of morbidity and mortality, consuming more health care resource than all other complications combined. Diabetic polyneuropathy and peripheral vascular disease constitute the two main risk factors, with trauma and foot infection being the most important i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 46 publications
(35 citation statements)
references
References 33 publications
2
33
0
Order By: Relevance
“…However, it is not going well, especially the management of diabetic complications, such as DFCs 21,22 . A previous study reported that the overall [23][24][25] . In our study, we observed a strong relationship between FHD and DFCs, especially of the different numbers of relatives with diabetes, in which the number of patients with one and more than 1 relative with diabetes led to 1.377-and 1.402-fold increases in the risk of DFCs, respectively, compared with those without FHD.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is not going well, especially the management of diabetic complications, such as DFCs 21,22 . A previous study reported that the overall [23][24][25] . In our study, we observed a strong relationship between FHD and DFCs, especially of the different numbers of relatives with diabetes, in which the number of patients with one and more than 1 relative with diabetes led to 1.377-and 1.402-fold increases in the risk of DFCs, respectively, compared with those without FHD.…”
Section: Discussionmentioning
confidence: 99%
“…A preexisting microangiopathic disease burden (and markers thereof, e.g. poor glycaemic control and duration of diabetes) are strong risk factors for disease severity ( 54 ). TMA is reported as a frequent event in Covid-19 and is likely to involve endothelium-mediated complement activation ( 55 ).…”
Section: Covid-19 and Thrombotic Microangiopathymentioning
confidence: 99%
“…Angiogenesis plays a significant role during the dynamic process of wound healing. In fact, DFU show areas of local skin ischemia with severely impaired blood flow ( Falanga, 2005 ; Sharma et al, 2020 ). Therefore, therapeutic angiogenesis, which aims at stimulating neovascularization through local delivery of angiogenic factors to improve the perfusion of ischemic tissue, is an attractive treatment strategy.…”
Section: Introductionmentioning
confidence: 99%